2000
DOI: 10.1016/s0014-5793(00)02302-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β‐arrestins in toxic and cold thyroid nodules

Abstract: L L-Arrestins mediate agonist dependent desensitization of G protein-coupled receptors. Somatic TSH receptor mutations were identified in the majority of hot thyroid nodules. When transiently overexpressed in COS 7 cells these mutations resulted in constitutive activation of the cAMP pathway. However, the in vivo mechanisms and the in vivo desensitization of these TSH receptor mutations are unknown. Moreover, constitutively activated L L-adrenergic receptors are known to be constitutively desensitized. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
2
20
0
2
Order By: Relevance
“…An upregulation of phosphodiesterases by cAMP has been observed previously in thyroid cells in vitro as well as in other systems (Nilson et al, 1980;Persani et al, 2000). Negative feedback in the adenoma cells is further provided by an upregulation of GRK5, which desensitizes the TSH receptor (Voigt et al, 2004), and by a minor downregulation of adenylylcyclase (Eszlinger et al, 2004). Cell heterogeneity and the great sensitivity of the cells to small cAMP rises (Neve and Dumont, 1970;Ketelbant-Balasse et al, 1976) might explain how the slightly increased averaged cAMP levels can sustain the increased activity and growth of thyrocytes.…”
Section: Discussionmentioning
confidence: 55%
“…An upregulation of phosphodiesterases by cAMP has been observed previously in thyroid cells in vitro as well as in other systems (Nilson et al, 1980;Persani et al, 2000). Negative feedback in the adenoma cells is further provided by an upregulation of GRK5, which desensitizes the TSH receptor (Voigt et al, 2004), and by a minor downregulation of adenylylcyclase (Eszlinger et al, 2004). Cell heterogeneity and the great sensitivity of the cells to small cAMP rises (Neve and Dumont, 1970;Ketelbant-Balasse et al, 1976) might explain how the slightly increased averaged cAMP levels can sustain the increased activity and growth of thyrocytes.…”
Section: Discussionmentioning
confidence: 55%
“…Finally, we found that our ATC/PDTC series had a deregulation of critical genes for thyroid hormone synthesis, such as the overexpression of ARRB2 (b-arrestin 2; Voigt et al, 2000), which is implicated in the desensitization of thyroid-stimulating hormone receptors (TSHR), the underexpression of RAB5A, which participates in the thyroglobulin production (TG; Croizet-Berger et al, 2002), and a diminished expression of TG and PAX8, which has also been observed before in ATC/PDTC series (Onda et al, 2004). Furthermore, the expression of HHEX, a gene related to thyroid morphogenesis and differentiation, was decreased in ATC/PDTC.…”
Section: Discussionmentioning
confidence: 86%
“…These different results can most likely be explained by defects in the RGS regulation pathway or by additional counter-regulatory pathways which occur in the chronically proliferating hot thyroid nodules. The increased expression of b-arrestin 2 in hot thyroid nodules (46) is possibly an example of such an additional counter-regulation. b-arrestin 2 desensitizes the TSHR followed by a blocked G protein coupling.…”
Section: Discussionmentioning
confidence: 99%